Enforcement and inequality in collective PES to reduce tropical deforestation: Effectiveness, efficiency and equity implications. (May 2022) - Naime, Julia; Angelsen, Arild; Molina-Garzón, Adriana; Carrilho, Cauê D.; Selviana, Vivi; Demarchi, Gabriela; Duchelle, Amy E.; Martius, Christopher
Highlights: Individual sanctions improve effectiveness, efficiency and equity of collective PES. Public monitoring of individual deforestation improves effectiveness and equity. External sanctions are the most robust policy to increase PES performance. Internal sanctions deliver on effectiveness but can reduce efficiency and equity. The effect of inequality on deforestation and policy performance varies across sites. Abstract: Collective Payments for Ecosystem Services (PES), where forest users receive compensation conditional on group rather than individual performance, are an increasingly used policy instrument to reduce tropical deforestation. However, implementing effective, (cost) efficient and equitable (3E) collective PES is challenging because individuals have an incentive to free ride on others' conservation actions. Few comparative studies exist on how different enforcement strategies can improve collective PES performance. We conducted a framed field experiment in Brazil, Indonesia and Peru to evaluate how three different strategies to contain the local free-rider problem perform in terms of the 3Es: (i) Public monitoring of individual deforestation, (ii) internal, peer-to-peer sanctions (Community enforcement) and (iii) external sanctions (Government enforcement). We also examined how inequality in wealth, framed as differences in deforestation capacity, affects policy performance. We find that introducing individual level sanctions can improve the effectiveness, efficiency and equity of collective PES, but there is no silver bullet that consistently improves all 3Es across country sites. Public monitoring reduced deforestation and improved the equity of the program in sites with stronger history of collective action. External sanctions provided the strongest and most robust improvement in the 3Es. While internal, peer enforcement can significantly reduce free riding, it does not improve the program's efficiency, and thus participants' earnings. The sanctioning mechanisms failed to systematically improve the equitable distribution of benefits due to the ineffectiveness of punishments to target the largest free-riders. Inequality in wealth increased group deforestation and reduced the efficiency of Community enforcement in Indonesia but had no effect in the other two country sites. Factors explaining differences across country sites include the history of collective action and land tenure systems.